Limitations and obstacles of the spontaneous adverse drugs reactions reporting: Two “challenging” case reports - Palleria, Caterina (Medknow Publications & Media Pvt Ltd, 2013)
INTRODUCTION: Nowadays, based on several epidemiological data, iatrogenic disease is an emerging public health problem, especially in industrialized countries. Adverse drugs reactions (ADRs) are extremely common and, therefore, clinically, socially, and economically worthy of attention. Spontaneous reporting system for suspected ADRs represents the cornerstone of the pharmacovigilance, because it allows rapid detection of potential alarm signals related to drugs use. However, spontaneous reporting system shows several limitations, which are mainly related to under-reporting. In this paper, we describe two particular case reports, which emphasize some reasons of under-reporting and other common criticisms of spontaneous reporting systems. MATERIALS AND METHODS: We performed a computer-aided search of Medline, PubMed, Embase, Cochrane library databases, national and international databases of suspected ADRs reports in order to identify previous published case reports and spontaneous reports about the ADRs reviewed in this paper, and to examine the role of suspected drugs in the pathogenesis of the described adverse reactions. RESULTS: First, we reported a case of tizanidine-induced hemorrhagic cystitis. In the second case report, we presented an episode of asthma exacerbation after taking bimatoprost. Through the review of these two cases, we highlighted some common criticisms of spontaneous reporting systems: under-reporting and false causality attribution. DISCUSSION AND CONCLUSION: Healthcare workers sometimes do not report ADRs because it is challenging to establish with certainty the causal relationship between drug and adverse reaction; however, according to a key principle of pharmacovigilance, it is always better to report even a suspicion to generate an alarm in the interest of protecting public health.